EFFECTS OF WORKING CAPITAL TURNOVER, CASH TURNOVER, AND RECEIVABLE TURNOVER ON PROFITABILITY - Amin, Andi Mustika; Riwayat Abadi, Rahmat; Tawe, Amiruddin; Rifadly Abadi, Ridfan; Paramaswary Aslam, Annisa (MOTIVASI, 2024)
Purpose– The level of competition between companies is increasing as the business develops, especially when there is intense competition between similar companies. The cigarette industry is growing and becoming increasingly competitive to improve its performance. The cigarette industry significantly reduces the return on assets every year, even though the cigarette industry is a source for the government because taxes and customs are state income and accommodate a large workforce. This study aims to determine the influence of working capital, cash, and receivable turnover on profitability. Design/methodology– The type of research used is an associated method with a quantitative approach. The population in this research is the annual reports of cigarette sub-sector manufacturing companies going public. Samples in this study were taken from 32 companies using a purposive sampling approach. The type of data used in this research is secondary data using financial report data from manufacturing companies in the cigarette industry subsectors in the 2015–2022 period. Multiple linear regression is the data analysis technique employed, while SPSS version 25 is the software used. Findings - The study results show that working capital turnover has no significant effect on profitability, cash turnover significantly affects profitability, and receivables turnover has no considerable impact on profitability.